O bloco de constitucionalidade: reconhecimento e conseqüências no sistema constitucional brasileiro - Vargas, Angelo Miguel de Souza (2007)
The phenomenon of the constitucionalization of the right and, mainly, the internationalization of the constitucional law, have demonstrated the necessity of a careful observance in the materiality of the rules of law. This analysis becomes essential in face from that, recognizing determined norm as constitutional, it will have to be excused, the imperatividade of the constitutional normative force, as product of the principle of the constitutional supremacy, the constitutional rigidity, and will serve, also, of paradigm for the constitutionality control. The recognition of the constitutional character of determined norms is of the constitutional document, attributes denomination to it of Block of Constitutionality. This scene has produced reflected in the Brazilian legal system, especially, in the protection of the basic rights, through the Constitutional Emendation nº 45 of 2004. However, part of the doctrine, in this includes our positioning, already it recognized that the Brazilian constitutional system, electing for a systematic and teleologic interpretation of its norms, prescribed since the promulgation of the Constitution of 1988 for the distant identification of constitutional ruleses of the constitutional text, with beddings in § 2º, of art. 5º, as well as in the implicit principles constitutional. Of this form, as the constitutional ruleses are identified from its materiality or constitutional formality, in the Brazilian constitutional system the admission of the constitutionality block finish for becoming undeniable, but some consequences happen of this observation. Of any form, the Brazilian jurisprudence meets in constant expansion allowing to interprets it to always protect the constitutional identity and the prevalence of the basic rights